Study on Runoff Debit in the Catchment Area of Waduk Gajah Mungkur Wonogiri - Anna, Alif Noor; Priyana, Yuli (Forum Geografi, 1991)
AbstractWater resource is one of natural resources, that is very vital. It needed to be used and to be kept throughly. For those purposes need good and directed plan, in which one of the basic component of it plan have to be supported by available a complete hydrological data and it analysis. One of hydrological data analysis is to estimate runoff of catchement area, which can be used for planning the hydrologi construction. This research aim: 1) to calculate the run off discharge by thornwaite Mather Method, monthly, annualy, and the average on the catchment through a sample of Keduang, Temon, Alang, and Wuryantoro areas; 2) to analyze the difference of the run off discharge (at no. 1) by observation resulted from trend analysis. Based on the calculation, it appears, thornwaite-mather method showed that high discharge (moreover limit 0) in dry month. From the research result, it appears, that calculation discharge graphic had lower differentation than observation discharge graphic. From sample of catchment areas that have been investigated, from the highest to the lowest deviation was Wuryantoro catchment area (78,8%), Temon catchment area (47,38%), Alang catchment area (46,45%), and Keduang catchment area (24,98%) respectively). The condition like above caused by intervation of man. Not only did he influence vegetatively, but he influenced technically as well. From these conservation, technical conservation (flood and construction and reservoir) was the highest influence to run off discharge calculation. The run off discharge that was calculated by thornthwite-Mather Method based on air temperate, rainy, altitude, and water holding capacity only, but groundwater supply didnât be calculated.